Effect of Anadara Granosa Shell Volume Fraction on Erosive Wear and Hardness Behaviour of Al 6061 Metal Matrix Composites - Riki Hendra Purba; Aldi Raditya Adriansyah; James Julian; Fitri Wahyuni; Elvi Armadani; Fathin Muhammad Mahdhudhu (Universitas Muhammadiyah Sidoarjo, 2026)
Despite the favorable mechanical properties of Anadara Granosa Shell (AGS), particularly hardness, its influence on the wear resistance of Metal Matrix Composites (MMCs) remains insufficiently explored. Therefore, this study aims to investigate the potential of AGS waste as an eco-friendly reinforcement for Al6061 alloy. Composites were fabricated with 0 wt%, 5 wt%, 10 wt%, and 15 wt% AGS addition. Wear behavior of each specimen was evaluated using sandblast with SiO2 as the erodent particles. The investigation also involved the microstructure and wear mechanism observation using optical microscope and Scanning Electron Microscopy (SEM). In addition, the hardness of each material measurement using Vickers hardness test was included to obtain a comprehensive insight. The results shows that the AGS reinforcement was evenly distributed within the matrix, though a minor presence of voids was observed. The hardness of specimens exhibited a consistent increase proportional to the AGS content. Interestingly, the erosion rate showed no significant difference between the 0 wt% and 5 wt% AGS additions, but drastically increased with 10 wt% and 15 wt% reinforcement. This suggests that hardness is not the primary factor governing the erosion behavior in these composites. Analysis of the worn surfaces revealed a prevalent wear mechanism: reinforcement particle peel-out, which became more severe at 10 wt% and 15 wt% AGS concentrations. Conversely, the unreinforced (0 wt%) Al 6061 alloy displayed ripple formation, indicating a plastic deformation mechanism typical of a ductile material. Therefore, this study highlights the critical importance of considering the wear mechanism, specifically the susceptibility to particle pull-out, when evaluating the erosive wear behavior of Al6061 MMCs reinforced with Anadara Granosa Shell waste.